Hydroboration of terminal olefins with pinacolborane catalyzed by new 2-iminopyrrolyl iron(ii) complexes. Issue 13 (24th May 2019) - Cruz, Tiago F. C.; Pereira, Laura C. J.; Waerenborgh, João C.; Veiros, Luís F.; Gomes, Pedro T.
Abstract : New Fe(ii ) mono(2-iminopyrrolyl) complexes catalyze the hydroboration of terminal olefins with pinacolborane via a borane oxidative addition pathway. Abstract : Four paramagnetic 14-electron tetracoordinated Fe(ii ) complexes of 5-substituted-2-iminopyrrolyl ligands of the type [Fe{κ 2 N, N′ -5-R-NC4 H2 -2-C(H)N(2, 6- i Pr2 -C6 H3 )}(Py)Cl], with R = 2, 6-Me2 -C6 H3 (1a ), 2, 4, 6- i Pr3 -C6 H2 (1b ), 2, 4, 6-Ph3 -C6 H3 (1c ) and CPh3 (1d ), were synthesized in moderate yields by reacting the respective 5-substituted-2-iminopyrrolyl potassium saltsKLa-d with FeCl2 (Py)4 in toluene. Complexes1a–d were characterized by 1 H NMR, FTIR spectroscopies, elemental analysis and by the Evans method, the corresponding effective magnetic moments showing a high-spin electronic nature. X-ray diffraction studies on complexes1a and1c showed distorted tetrahedral coordination geometries. Complexes1a–c, activated with K(HBEt3 ), were efficient catalyst systems for the hydroboration of several terminal alkenes with pinacolborane in good to high yields (50–90%). This system mainly yielded the respective anti-Markovnikov addition products, except when styrenes were used. A screening of the hydroboration of styrene catalyzed by complexes1a–c activated with K(HBEt3 ) showed that the selectivity in the Markovnikov product increased with increasing steric bulkiness of the R group, exhibiting selectivities up to 91%. Additionally, the stoichiometric reaction of complex1b with K(HBEt3 ) over 30 minutes yielded the mixture of hydride species2 and22 (mixture I). On the other hand, when reacting the same components over 16 h, the Fe(i ) complex3 was also identified in the mixture, in addition to2 +22 (mixture II). These mixtures were characterized in solution by the Evans method and in the solid state by elemental analysis, 57 Fe Mössbauer and FTIR spectroscopies, compounds22 and3 being also analyzed by X-ray diffraction. These results suggest that the corresponding catalytic cycle follows the borane oxidative addition route to a Fe(i ) species.